EVALUASI PENGAKUAN DAN PENGUKURAN TRANSAKSI PEMBIAYAAN DENGAN PRINSIP BAGI HASIL DALAM KONSEP AKUNTANSI PERBANKAN SYARIâAH (Studi Kasus Bank Muamalat Indonesia Tbk Cabang Semarang) - ANDINI, RITA (STIE Totalwin Semarang, 2011)
The purpose of this study was to evaluate whether the recognition and measurement principles for the financing transaction with the results in the concept of Sharia banking accounting is applied in Semarang Branch of Muamalat Indonesia Bank has been in accordance with PSAK No. 59 or not. Qualitative analysis methods used in this study carried out by analyzing the recognition and measurement results in a financing transaction for the accounting concept of Sharia in Semarang Branch of Muamalat Indonesia Tbk and perform the implementation of comparative evaluation in practice with financial reporting standards in this regard to PSAK no.59 about sharia banking accounting. Treatment for the execution of financing transactions between existing implementations on Muamalat Indonesia Tbk in Semarang Branch with PSAK number 59 of shariah banking accounting was appropriate